2019
DOI: 10.4018/978-1-5225-5799-9.ch003
|View full text |Cite
|
Sign up to set email alerts
|

The Implicit Pedagogy and the Hidden Curriculum in Postmodern Education

Abstract: This chapter addresses everyday educational practices known as the “hidden curriculum” and the related term “implicit pedagogy” in today's dominant postmodern theory. It presents results of a survey with preschool and school teachers (N=813) in Croatia and Slovenia in selected three determinants of the hidden curriculum: empathy, personality traits, and preschool and school teachers' attitudes towards space characteristics. In addition to interesting results describing current conditions in these vital populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The more complex and differentiated descriptions represented the postmodern understanding of the hidden curriculum mainly as subjective theories, implicit beliefs, and tacit knowledge (Apple, 1990;Jančec & Lepičnik-Vodopivec, 2019;Jug Došler, 2021;Kroflič, 2005;Skelton, 1997). The counsellors focused on identifying the hidden cu rri culum as subjective theories, implicit beliefs, and tacit knowledge in teachers, but only exceptionally in their own work.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The more complex and differentiated descriptions represented the postmodern understanding of the hidden curriculum mainly as subjective theories, implicit beliefs, and tacit knowledge (Apple, 1990;Jančec & Lepičnik-Vodopivec, 2019;Jug Došler, 2021;Kroflič, 2005;Skelton, 1997). The counsellors focused on identifying the hidden cu rri culum as subjective theories, implicit beliefs, and tacit knowledge in teachers, but only exceptionally in their own work.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, we emphasize the importance of dealing with the hidden curriculum during the initial and continuing education/training of school counsellors and other educators. Jančec and Lepičnik-Vodopivec (2019) have shown that there is a tangible part of the hidden curriculum that can be quantified using standardized questionnaires. The interpretation of the findings can be applied during candidate selection and professional training programmes to help stimulate the acquisition of new knowledge and beliefs, and also to improve educators' daily work as well as their subjective and implicit theories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations